How The Characteristics of The Board of Commissioners Affect ESG Shariah Issuers in Indonesia Period 2020-2023 - Nurhaliza Nurhaliza; Hafas Furqani; Rina Desiana; Abbas Paliket (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2026)
Purpose:Investment based on Environmental, Social, and Governance (ESG) continues to grow rapidly globally, including in Indonesia. However, ESG disclosure in Indonesia is still low, with only a small number of issuers included in the ESG index. The implementation of ESG can enhance profitability, company value, and meet stakeholder expectations. This study examines the influence of gender diversity, board size, and independent board members on ESG disclosure in companies listed on the Sharia stock index in Indonesia for the period 2020-2023.Design/Methodology:With a quantitative approach, panel data from 104 observations were analyzed using multiple linear regression.Findings:The research results show that gender diversity on the board of commissioners has a positive impact on ESG disclosure, the size of the board of commissioners has a negative impact on ESG disclosure, and independent board of commissioners does not have an impact on ESG disclosure. Simultaneously, gender diversity on the board of commissioners, the size of the board of commissioners, and independent commissioners influence ESG disclosure.Practical Implications:Sharia companies in Indonesia need to promote gender diversity and maintain an efficient board size to enhance ESG disclosure, while ensuring a balanced board composition to uphold the company's credibility and integrity according to ESG standards.Originality/Value:This research provides an analysis of the characteristics of the Board of Commissioners influencing Sharia ESG issuers in Indonesia